2023
DOI: 10.1101/2023.11.16.566902
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SAP expressing T peripheral helper cells identify systemic lupus erythematosus patients with lupus nephritis

Yevgeniya Gartshteyn,
Laura Geraldino-Pardilla,
Leila Khalili
et al.

Abstract: IntroductionT follicular (TFH) and peripheral helper (TPH) cells have been increasingly recognized as a pathogenic subset of CD4 T cells in systemic lupus erythematosus (SLE). The SLAM Associated Protein (SAP) regulates TFH and TPH function by binding to the co -stimulatory signaling lymphocyte activation molecule family (SLAMF) receptors that mediate T cell – B cell interactions. SAP and SLAMF are critical for TPH dependent B cell maturation into autoantibody-producing plasma cells that characterize SLE patho… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
(41 reference statements)
0
1
0
Order By: Relevance
“…However, only small differences in cell surface SLAMF expression levels have been described in SLE compared to controls, which are not consistently seen across studies (4)(5)(6). We found that SLAMF3 and SLAMF6 expression can be detected on 98% of circulating T cells in SLE and healthy controls (7). Therefore, we hypothesized that the receptor's cell-surface expression does not regulate SLAM signaling, and instead, SLAM's role in SLE is modulated by downstream adaptors.…”
Section: Introductionmentioning
confidence: 76%
“…However, only small differences in cell surface SLAMF expression levels have been described in SLE compared to controls, which are not consistently seen across studies (4)(5)(6). We found that SLAMF3 and SLAMF6 expression can be detected on 98% of circulating T cells in SLE and healthy controls (7). Therefore, we hypothesized that the receptor's cell-surface expression does not regulate SLAM signaling, and instead, SLAM's role in SLE is modulated by downstream adaptors.…”
Section: Introductionmentioning
confidence: 76%